HUBUNGAN KINERJA GURU DENGAN HASIL BELAJAR GEOGRAFI SISWA - Pradita Yulia Valentina; Sumadi Sumadi; Nani Suwarni (JPG (Jurnal Penelitian Geografi), 2014)
This study aims to determine the relationship of the teacher performance to the student geography learning outcomes. This study uses correlation. Samples numbered 44 students from the student population of 105 and were taken using a proportional random sampling technique. Data collection techniques are using the techniques of documentation, interviews and questionnaires. Analysis of the data is using the product moment formula as hypotheses testing that have been proposed. Based on data analysis, the results obtained are as follows: (1) There is a positive relationship a close and significant correlation between the performance of teachers in planning the learning with the students result learning geography. (2) There is a positive relationship, strong and significant correlation between the performance of teachers in implementing the learning of students geography learning outcomes. (3) There is a positive relationship, strong and significant correlation between teacher performance in evaluating learning process of students learning geography.Penelitian ini bertujuan untuk mengetahui hubungan kinerja guru dengan hasil belajar geografi siswa. Penelitian ini menggunakan metode korelasi. Sampel berjumlah 44 siswa dari populasi 105 siswa dan diambil menggunakan teknik proporsional random sampling. Teknik pengumpulan data menggunakan teknik dokumentasi, wawancara dan kuesioner. Analisis data menggunakan rumus product moment sebagai pengujian hipotesis yang telah diajukan. Berdasarkan analisis data, hasil yang diperoleh sebagai berikut: (1) Ada hubungan yang positif, erat dan signifikan antara kinerja guru dalam merencanakan pembelajaran dengan hasil belajar geografi siswa. (2) Ada hubungan yang positif, erat dan signifikan antara kinerja guru dalam melaksanakan pembelajaran dengan hasil belajar geografi siswa. (3) Ada hubungan yang positif, erat dan signifikan antara kinerja guru dalam evaluasi pembelajaran dengan hasil belajar geografi siswa.Kata kunci: guru, hasil belajar siswa, kinerja.